Annual Review and Planning meeting - Accelerating Impacts of CGIAR Climate Research for Africa (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
The Annual Review and Planning Meeting Report for AICCRA-Senegal 2024 details the progress and strategic planning for the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) project in Senegal. The report highlights the project's efforts to enhance the accessibility and utilization of climate information services (CIS) and climate-smart agriculture (CSA) technologies. The workshop focused on evaluating achievements, formulating the 2024 action plan, and fostering collaboration among stakeholders. Key discussions included transitioning from access to use of CSA/CIS, gender and social inclusion, and developing sustainable business models. Partners presented their achievements and plans, emphasizing capacity building, technology dissemination, and integration with national programs. The meeting underscored the importance of evidence-based approaches and multi-actor partnerships to ensure the project's sustainability and impact on smallholder farmers and broader agro-sylvo-pastoral landscapes.